Professional activity. How is family physicians' work time changing? - Woodward, C. A. (2001)
OBJECTIVE: To examine hours worked professionally, work preferences, and changes in both of these and their correlates. DESIGN: Repeated surveys done in 1993 and 1999. SETTING: Ontario family practices. PARTICIPANTS: Cohort of physicians certified in family medicine between 1989 and 1991 after family medicine residency who were surveyed in 1993 when they resided in Ontario. MAIN OUTCOME MEASURES: Self-reported hours spent weekly on professional activities, desired hours of professional work, and balance between work and other activities. RESULTS: Fifty-three percent (293) of 553 physicians responded to the 1999 survey; 91% had remained family physicians; 85% of these had participated in the 1993 survey. The difference between the hours that family physicians preferred to work professionally and their actual hours of work had increased since 1993. Childless physicians, women physicians with preschool children, and women physicians married to other physicians worked fewer hours professionally than other physicians in 1999. Female physicians and physicians without children worked closer to their preferred hours than other physicians. Reporting a preference to work fewer hours professionally in 1993 was linked with a reduction in professional activities by 1999. CONCLUSION: Greater attention should be paid in physician resource planning to the family life cycle of female physicians. Lifestyle changes could lead to a reduction in professional activity among these physicians.